Intranodal palisaded myofibroblastoma arising from parotid gland: A case report of an unusual origin - Hanadi Fatani; Abdulhadi Alsamman; Abdulsalam AlJabab; Sadiq Al Dandan (Elsevier, 2018)
Intranodal palisaded myofibroblastoma (IPM) is a rare benign mesenchymal tumor of hybrid smooth muscle and fibroblastic cell features. It is characterized by hemorrhagic spindle cell proliferation, with amianthoid stromal formation in lymph node. The precise etiology and pathogenesis of this entityis not yet explained well. Previous examples were reported in adults and mainly in inguinal and rarely in the peritoneal cavity. To our knowledge this is the first occurrence to be reported in the parotid gland of a 7-year-old male. Keywords: Intranodal palisaded myofibroblastoma, Amianthoid fibers, Lymph node, Peritoneal cavity